On the theory of economic policy - Tinbergen, Jan (Amsterdam : North-Holland Pub. Co., 1952)
This booklet attempt to deal systematically with a number of problems of economic policy. On one hand the attempt consists of a distinction between the various classes of variables characteristic of the problems of economic policy and of a mathematical formulation of the type of problems involved. It furthers attempts to supply a systematic survey of the various types of economic policy from simple every-day decisions to social and economic reforms.
rpm 26/09/2017
Loans
Keywords: Economic policy